Some Dynamic and Comparative Static Properties of a Spatial Model of Production - Miyao, Takahiro (Review of Economic Studies, 1977)
Journal Article Some Dynamic and Comparative Static Properties of a Spatial Model of Production Get access Takahiro Miyao Takahiro Miyao University of California, Santa Barbara Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 2, June 1977, Pages 321–327, https://doi.org/10.2307/2297069 Published: 01 June 1977